Recurrent nasopharyngeal rhinosporidiosis: Case report from Qatar and review of the literature - Gawahir M. Ali (17115724) (2020)
Rhinosporidiosis is a chronic granulomatous infectious disease that predominantly affects the mucosal membranes of the nose and nasopharynx. The disease is caused by Rhinosporidium seeberi, an eukaryotic pathogen with distinct geographical distribution particularly in tropical and subtropical areas acquired mainly through aquatic exposure. We report a case of a young Nepalese male who presented with recurrent right nasopharyngeal mass where surgical excision and histopathological examination confirmed the diagnosis following distinct pathognomonic findings. There is no optimal effective management of the disease and surgical excision coupled with cauterization to prevent recurrence is the recommended best option since medical treatment alone is ineffective. The clinical presentation, assessment and management options are reviewed. Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2020.e00901